Seroprevalence, risk factors, and therapeutic response of feline panleukopenia in household cats at Savar Upazila of Dhaka district in Bangladesh (Asian Journal of Medical and Biological Research, 2024)
Feline panleukopenia is a single-stranded DNA virus. It is a highly contagious and often lethal viral infection in cats. The present study aimed to determine the seroprevalence, associated common risk factors, and therapeutic response of the disease in cats in the study area. The disease was diagnosed based on history, characteristic clinical findings, and laboratory diagnosis by a Rapid diagnosis test kit. Information on age, season, sex, and immune status was evaluated to determine the risk factors of feline panleukopenia virus infection in cats. The present investigation showed that 58.33% of cats tested positive for FPV. In addition, cats under the age of six months had a greater incidence of infection (67.12%) than cats between the ages of seven and twelve months (59.18%) and cats over twelve months (38.24%). Winter (68.18%) had a higher prevalence of FPV than summer (52.83%) and rainy (48.65). In the present study, male cats had a higher frequency of FPV (60.49%) than female cats (56%). The non-vaccinated cats exhibited FPV positive (62.96%) compared to vaccinated cats (28.57%).  In addition, 42 (46.15%) animals had full recovery from infection. The recovery rate (65.52%) of cats aged 7 to 12 months was higher than that of two other age groups. Additionally, more cats were recovered in the summer season (64.29%) than in the winter (33.33%) or during the rainy season (50%). Compared to non-vaccinated cats (44.71%), FPV-positive vaccinated animals have demonstrated a higher recovery percentage (66.66%). Proper hygienic management and vaccination are important measures to check the FPV infection in cats. The status of the prevalence and associated risk factors is necessary to control the fatal infection of cats in the study area.Asian J. Med. Biol. Res. 2024, 10(4), 141-147